Awareness and knowledge regarding emergency contraception in Berlin adolescents. (2nd January 2017) - von Rosen, Frederik T.; von Rosen, Antonella J.; Müller-Riemenschneider, Falk; Tinnemann, Peter
Abstract: Background: Lack of information has been described as a major factor in non-use of oral emergency contraception (EC) following unprotected intercourse. Despite the ongoing vociferous debate on liberalisation of access, little evidence is available on EC knowledge in Germany, particularly among adolescents. Methods: We conducted a cross-sectional survey among ninth graders in convenience sample of 13 Berlin schools. We assessed perceived and actual knowledge on the effectiveness, timeframe and availability of EC and on pregnancy risk in six scenarios. Results: A total of 1177 students between 13 and 16 years of age participated. Mean age was 14.6 years (standard deviation 0.67); 51.4% of participants were male. Whilst 8.7% had never heard of EC, 38.6% knew of its effectiveness, but only 12.7% knew the timeframe for EC. Of the sources of EC, only gynaecologists were widely known. Most students correctly evaluated pregnancy risk in given scenarios. Girls were more knowledgeable on most topics except for pregnancy risk. Attending a school of lower academic standard and being of immigrant background was associated with lower knowledge on the majority of items. Conclusions: Generally, students were aware of the existence of EC, but many lacked the knowledge of when to take it and how to access it. Especially in the light of the recent liberalisation of EC access in Germany, increased educational efforts are warranted to ensure that the population has the knowledge necessary to make a truly informed choice regarding its use.